Effects of expanding a non-contributory health insurance scheme on out-of-pocket healthcare spending by the poor in Turkey - Rifat Atun; Abdullah Tirgil; William T Dickens (BMJ Global Health)
Introduction Insufficient or no health insurance creates financial access barriers to healthcare services, especially for vulnerable populations. The Green Card scheme, a non-contributory government-funded health insurance scheme for the poor in Turkey, was expanded in 2003–2006 and has provided citizens with extended benefits. We study the effects of this expansion of the Green Card scheme on out-of-pocket healthcare expenditures for low-income households.Methods We use difference-in-differences study design to examine the causal impact of having a Green Card on financial protection in terms of out-of-pocket health expenditures and catastrophic expenditures for the poor in Turkey. In addition, we implement quantile regression analysis to examine how the benefits expansion affects the poor who have the largest out-of-pocket expenditures and are in the upper tail of the health spending distribution.Results We find that the expansion of benefits coverage leads to significant reductions in annualised out-of-pocket healthcare expenditures for dental care, diagnostics services, pharmaceuticals and total medical spending. We show that the decline in spending by Green Card beneficiaries corresponds to about 33% as per cent of total per-household medical spending. Quantile regression analysis shows that the scheme is even more effective at reducing expenditures for those people facing large health expenditures. The scheme reduces the incidence of catastrophic expenditures by nearly 50% among those with the largest annual out-of-pocket expenditures.Conclusions Increasing benefits coverage for a non-contributory insurance programme leads to financial protection for the poor by reducing out-of-pocket and catastrophic health expenditures. It is even more effective at reducing out-of-pocket health spending for those whose health expenditures that lie on the high end of healthcare spending distribution.